The history of US-Japan relations : - Kimura, Kan (Singapore, 2017)
It examines the emergence of Japan in the wake of the 1905 Russo-Japanese War and the development of U.S. policies toward East Asia at the turn of the century. It goes on to study the impact of World War One in Asia, the Washington Treaty System, the issue of Immigration Issue and the deterioration of US-Japan relations in the 1930s as Japan invaded Manchuria. It also reflects on the Pacific War and the Occupation of Japan, and the country’s postwar Resurgence, democratization and economic recovery, as well as the maturing and the challenges facing the US Japan relationship as it progresses into the 21st century. This is a key read for those interested in the history of this important relationship as well as for scholars of diplomatic history and international relations.